BNT162b2 booster after heterologous prime-boost vaccination induces potent neutralizing antibodies and T cell reactivity against SARS-CoV-2 Omicron BA.1 in young adults - Seidel, Alina; Zanoni, Michelle; Groß, Rüdiger; Krnavek, Daniela; Erdemci-Evin, Sümeyye; von Maltitz, Pascal; Albers, Dan P. J.; Conzelmann, Carina; Liu, Sichen; Weil, Tatjana; Mayer, Benjamin; Hoffmann, Markus; et al. (Frontiers in Immunology, 2022)
In light of the decreasing immune protection against symptomatic SARS-CoV-2 infection after initial vaccinations and the now dominant immune-evasive Omicron variants, ‘booster’ vaccinations are regularly performed to restore immune responses. Many individuals have received a primary heterologous prime-boost vaccination with long intervals between vaccinations, but the resulting long-term immunity and the effects of a subsequent ‘booster’, particularly against Omicron BA.1, have not been defined. We followed a cohort of 23 young adults, who received a primary heterologous ChAdOx1 nCoV-19 BNT162b2 prime-boost vaccination, over a seven-month period and analysed how they responded to a BNT162b2 ‘booster’. We show that already after the primary heterologous vaccination, neutralization titers against Omicron BA.1 are recognizable but that humoral and cellular immunity wanes over the course of half a year. Residual responsive memory T cells recognized spike epitopes of the early SARS-CoV-2 B.1 strain as well as the Delta and BA.1 variants of concern (VOCs). However, the remaining antibody titres hardly neutralized these VOCs. The ‘booster’ vaccination was well tolerated and elicited both high antibody titres and increased memory T cell responses against SARS-CoV-2 including BA.1. Strikingly, in this young heterologously vaccinated cohort the neutralizing activity after the ‘booster’ was almost as potent against BA.1 as against the early B.1 strain. Our results suggest that a ‘booster’ after heterologous vaccination results in effective immune maturation and potent protection against the Omicron BA.1 variant in young adults.